Said Nursi’s cause-wisdom congruence method as a method of social analysis - Sadettin Orhan (Cogent Social Sciences)
Is it possible to analyze social reality outside a secular, positivist and materialist perspective? Is it possible to understand and explain social phenomena and events with a methodology other than cause-effect determinism? Does revelation-centered thought provide us with this opportunity and methodology? These questions are the main motivational element of this study. I will seek the answers to these questions in the context of the cause-wisdom congruence method of Said Nursi, an Islamic scholar and Qur’an commentator. The methodology in question, which will be presented for the first time in this study, is based on evaluating the possibilities of reason and revelation together, going beyond the secular understanding of knowledge and science in analyzing social reality. Within the study’s limitations, application examples of Nursi’s methodology are also included. I hope that this method, which can also be described as the sociology of wisdom, will add new dimensions to interdisciplinary discussions, especially sociology.